Optimal Pensions in Aging Economies - Burkhard Heer (Center for Economic Studies and ifo Institute (CESifo), 2015)
Ýmrohoroðlu, Ýmrohoroðlu and Joines [1995, A life-cycle analysis of Social Security, Economic Theory, vol. 6, 83-114] show that the optimal replacement ratio of the payas-you-go public pension system in the US economy amounts to 30%. We extend their analysis to a model that 1) replicates the empirical wage heterogeneity, 2) endogenizes the individual's labor supply decision and 3) accounts for contributions-defined pensions of the US social security system. With these more realistic modifications, the optimal replacement ratio is found to amount to approximately 5% and to be insensitive with regard to the aging of the US population; however, lower productivity growth would result in higher optimal pension payments. In addition, the optimal pension scheme is found to be more progressive than the present US pension system.
Keywords: C68; D31; D91; H55; J11; J26; 330; optimal social security; progressive pensions; income and wealth distribution; demographic transition